Platinated DNA oligonucleotides: new probes forming ultrastable conjugates with graphene oxide - Wang, Feng; Liu, Juewen (Royal Society of Chemistry, 2014)
Metal containing polymers have expanded the property of polymers by involving covalently associated metal complexes. DNA is a special block copolymer. While metal ions are known to influence DNA, little is explored on its polymer property when strong metal complexes are associated. In this work, we study cisplatin modified DNA as a new polymer and probe. Out of the complexes formed between cisplatin–A15, HAuCl4–A15, Hg2+–T15 and Ag+–C15, only the cisplatin adduct is stable under the denaturing gel electrophoresis condition. Each Pt–nucleobase bond gives a positive charge and thus makes DNA a zwitterionic polymer. This allows ultrafast adsorption of DNA by graphene oxide (GO) and the adsorbed complex is highly stable. Non-specific DNA, protein, surfactants and thiolated compounds cannot displace platinated DNA from GO, while non-modified DNA is easily displaced in most cases. The stable GO/DNA conjugate is further tested for surface hybridization. This is the first demonstration of using metallated DNA as a polymeric material for interfacing with nanoscale materials.
Keywords: DNA; graphene oxide; oligonucleotides; Platinum